2018
DOI: 10.1002/hep4.1228
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry Confirms Fibrosis Regression From Sustained Virologic Response to Direct‐Acting Antivirals for Hepatitis C

Abstract: Sustained virologic response (SVR) after direct‐acting antiviral (DAA) therapy for chronic hepatitis C results in significant decreases in liver stiffness measured by transient elastography (TE). The aim of this study was to clarify if TE can guide post‐SVR management in patients with advanced fibrosis or cirrhosis prior to treatment as current guidelines are unclear on the role of TE after SVR. In total, 84 patients with hepatitis C virus and advanced fibrosis or cirrhosis and from a single center underwent D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 26 publications
2
34
0
1
Order By: Relevance
“…In fact, in the Pan et al study, it was found that most of the patients whose LSM improved during followup still had advanced fibrosis or cirrhosis in liver biopsies. 4 TA B L E 1 ALT, FIB-4 and liver stiffness measurement (LSM) before and after sustained virological response (SVR) with liver histological results from ten patients they found substantial differences between both pre-and post-SVR…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In fact, in the Pan et al study, it was found that most of the patients whose LSM improved during followup still had advanced fibrosis or cirrhosis in liver biopsies. 4 TA B L E 1 ALT, FIB-4 and liver stiffness measurement (LSM) before and after sustained virological response (SVR) with liver histological results from ten patients they found substantial differences between both pre-and post-SVR…”
Section: Discussionmentioning
confidence: 93%
“…Changes in LSM may be due to a fast decrease in liver inflammation, but, in the long term, they might be explained by narrowing of fibrotic septa related to a reduction of collagen content, despite still having histological cirrhosis. In fact, in the Pan et al study, it was found that most of the patients whose LSM improved during follow‐up still had advanced fibrosis or cirrhosis in liver biopsies . However, they found substantial differences between both pre‐ and post‐SVR biopsies: (1) there was an improvement in liver inflammation in 73% of patients, and (2) there was improvement in sinusoidal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, fibrous bundles/septa bridging between portal tracts became thin, possibly suggesting regression of liver fibrosis. Pan et al [8] reported that among 15 patients with advanced fibrosis or cirrhosis (F3/F4) according to a pre-SVR liver biopsy who underwent a repeat biopsy post-SVR, only 4 patients showed improvement with F1-to-F2 fibrosis, whereas 11 patients still showed F3-to-F4 fibrosis. Nonetheless, morphometric analyses of the first 11 biopsied patients revealed that collagen content declined by an average of 46% over varying time intervals in 10 patients.…”
mentioning
confidence: 99%